Which water counts? blue and green water use and productivity in the Narmada Basin - Kumar, M. Dinesh; Singh, Om Prakash (International Water Management Institute, 2005)
Research highlight based on a paper titled ?The blue and green water use and productivity in agriculture: Study from Narmada River Basin, Madhya Pradesh, India.?